Success for sunnhemp - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
In Tanzania, the tropical legume Crotalaria ochroleuca, known as sunnhemp, is showing promise as a soil improver and fertilizer. It boosts crop yields, makes an effective weed suppressant, provides fodder for dairy animals (resulting in higher milk...